Harmonizing Sharia-Based Halal Standards with International Trade Law: A Comparative Legal Study - Deviana Yuanitasari; Nun Harrieti; Yamudin Salaeh (Faculty of Law Universitas Lampung, 2025)
The globalization of trade has elevated Islamic halal standards within the domain of international economic law. While halal certification is rooted in Sharia, World Trade Organization (WTO) law is governed by secular principles, including non-discrimination, Most-Favored Nation (MFN) treatment, and national treatment. This article conducts a comparative legal analysis of the potential tensions and compatibilities between these normative systems. Drawing on doctrinal and comparative methods, it examines how halal regulations in Muslim-majority and non-Muslim countries interact with WTO rules, particularly the SPS Agreement, TBT Agreement, and GATT 1994. The study argues that halal requirements, while potentially constituting non-tariff barriers, can be justified under WTO exceptions when aligned with legitimate objectives such as public morals and consumer protection. It also highlights the risk of discriminatory treatment when certification is applied selectively or instrumentally. The paper concludes with normative recommendations to reconcile Sharia-based halal frameworks with global trade norms, emphasizing mutual recognition, standard harmonization, and dialogue between religious and secular legal systems.